Temporal and spatial variation of richness and abundance of the community of birds in the Pantanal wetlands of Nhecolandia (Mato Grosso do Sul, Brazil) - Donatelli, Reginaldo Jose [UNESP]; Eaton, Donald P.; Sementili-Cardoso, Guilherme [UNESP]; Vianna, Renata Marques [UNESP]; Gerotti, Raphael Whitacker [UNESP]; Rodrigues, Fernanda Goncalves [UNESP]; Martins, Rafael Martos [UNESP] (Revista De Biologia Tropical, 2017)
The Pantanal wetlands represent one of the largest flood plains in the World, with extreme climatic variations between dry and wet seasons. The area shelters a high diversity of habitats, representing the main formations found in this sub-region: grasslands, savannah, forested savannah, riparian forests, bays and salines, and Negro river itself. This habitat variability determines the structure and dynamics of the bird community, because most species are closely related to specific habitats. For this, we studied the abundance of bird species from 2001 to 2004 in a Pantanal area of Fazenda Rio Negro, Aquidauana, Brazil. The abundance was compared among those four consecutive years, seasons (dry and wet), time of the day (morning and afternoon), and also between seven different habitats, in order to determine the variation in distribution patterns and habitats used by birds. For this, we used the linear transect method in each of the seven habitats, and recorded bird abundances to obtain richness. The richness registered in the mosaic of habitats was of 201 species for the savannah, 87 in forested savannah, 116 in the riparian forest, 75 in grasslands, 120 in bays, 92 in the salines and 64 in the Negro river, accounting for 348 species in the Pantanal of Rio Negro. Overall, 98 species of migratory birds were registered. The results highlighted some important issues regarding the total abundance of birds in Nhecolandia: Psittacidae was the most abundant family in the region, with prominence in all environments. Recurvirostridae, a monospecific family, showed expressive abundance due to the dominance of Himantopus mexicanus in the salinas, followed by Ardeidae, Anatidae and Cracidae. Other families with high abundance were Tyrannidae, Columbidae, Thraupidae and Emberizidae, all in predominantly terrestrial environments. Moreover: a) The highest number of specimens was recorded in the morning period and in the dry season, regardless of the habitat; b) there were no differences in abundance in the same habitat along the years, but the abundance was different among habitats. In general, the results indicated that there is a relatively stable bird population in each habitat along the annual cycle, but there were differences in abundance among habitats. Thus, additional studies on food availability in dry and wet seasons should be better explored in the future, either in this region or in other Pantanal regions. This fact could better explain the seasonal dynamics of the richness and abundance of birds in the Pantanal area in general.
Keywords: pantanal; bird community; mosaic of habitats; Mato Grosso do Sul